2023
DOI: 10.3390/healthcare11091281
|View full text |Cite
|
Sign up to set email alerts
|

Family Socioeconomic Status and Parental Involvement in Chinese Parents of Children with Autism Spectrum Disorder: A Moderated Mediation Model

Abstract: Parental involvement benefits children with autism spectrum disorder (ASD) in multiple developmental areas. We conducted the present study to examine the role of parenting stress and ASD symptom severity in the relationship between family socioeconomic status (SES) and parental involvement. A total of 165 Chinese parents of children with ASD participated in this study. Mediation analyses indicated that family SES was positively related to parental involvement; parenting stress partially mediated the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…29 Previous studies showed that parents with higher SES tend to be more attentive and knowledgeable about autism, have greater access to quality healthcare services and exhibit greater parental involvement. [30][31][32] This may lead to superior outcomes than individuals with ASD that did not receive a diagnosis or clinical attention. Besides, those with earlier diagnosis may have more frequent encounters with the healthcare system, which could explain why the younger age group with ASD had lower mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…29 Previous studies showed that parents with higher SES tend to be more attentive and knowledgeable about autism, have greater access to quality healthcare services and exhibit greater parental involvement. [30][31][32] This may lead to superior outcomes than individuals with ASD that did not receive a diagnosis or clinical attention. Besides, those with earlier diagnosis may have more frequent encounters with the healthcare system, which could explain why the younger age group with ASD had lower mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…Low socioeconomic status leads to increased parental stress, resulting in less involvement in the education of children with ASD. Parents may feel frustration and stress, also associated with growing costs arising from the need to allocate significant amounts of money for rehabilitation, which can hinder their fulfillment of parental duties and, consequently, result in less engagement in the education of their children with ASD [21]. Results regarding the impact of parental education on the risk of ASD are inconclusive and may require further research [32].…”
Section: Familial Socioeconomic Statusmentioning
confidence: 99%